Less invasive ventricular reconstruction for ischaemic heart failure. (3rd December 2019) - Klein, Patrick; Anker, Stefan D.; Wechsler, Andrew; Skalsky, Ivo; Neuzil, Petr; Annest, Lon S.; Bifi, Mauro; McDonagh, Theresa; Frerker, Christian; Schmidt, Tobias; Sievert, Horst; Demaria, Anthony N.; et al.
ABSTRACT: Aims: Surgical ventricular reconstruction to remodel, reshape, and reduce ventricular volume is an effective therapy in selected patients with chronic heart failure (HF) of ischaemic aetiology. The BioVentrix Revivent TC System offers efficacy comparable to conventional surgical ventricular reconstruction and is less invasive utilizing micro‐anchor pairs to exclude scarred myocardium on the beating heart. Here, we present 12‐months follow‐up data of an international multicenter study. Methods and results: Patients were considered eligible for the procedure when they presented with symptomatic HF [New York Heart Association (NYHA) class ≥II], left ventricular (LV) dilatation and dysfunction caused by myocardial infarction, and akinetic and/or dyskinetic transmural scarred myocardium located in the anteroseptal, anterolateral, and/or apical regions. A total of 89 patients were enrolled and 86 patients were successfully treated (97%). At 12 months, a significant improvement in LV ejection fraction (29 ± 8% vs. 34 ± 9%, P  < 0.005) and a reduction of LV volumes was observed (LV end‐systolic and end‐diastolic volume index both decreased: 74 ± 28 mL/m 2 vs. 54 ± 23 mL/m 2, P  < 0.001; and 106 ± 33 mL/m 2 vs. 80 ± 26 mL/m 2, respectively, P  < 0.0001). Four patients (4.5%) died in hospital and survival at 12 months was 90.6%. At baseline, 59% of HF patients were in NYHA class III compared with 22% at 12‐month follow‐up. Improvements in quality of life measures (Minnesota Living with Heart Failure Questionnaire 39 vs. 26 points, P  < 0.001) and 6‐min walking test distance (363 m vs. 416 m, P  = <0.001) were also significant. Conclusions: Treatment with the Revivent TC System in patients with symptomatic HF results in significant and sustained reduction of LV volumes and improvement of LV function, symptoms, and quality of life.